Effects of thermal and physical modification on functional properties of organosolv lignin from sugarcane bagasse and its application in cosmeceutical products - Chotirotsukon, Chayanon; Jirachavala, Kunlanis; Raita, Marisa; Pongchaiphol, Suchat; Hararak, Bongkot; Laosiripojana, Navadol; Champreda, Verawat (Frontiers in Chemical Engineering, 2023)
Organosolv lignin is an emerging bio-additive for creating functional properties in various products with its advantages in high-purity, sulfur-free, biocompatibility, and solubility in green solvents. In this study, effects of thermal and physical modification on alterations of functional properties and particle size distribution of isolated organosolv lignin from sugarcane bagasse (OLB) were studied. Thermal treatment of OLB at increasing temperatures from 170-230oC in 70%w/w aqueous ethanol led to alteration of phenolic hydroxyl content while ultrasonication resulted in homogeneous size distribution of the modified OLB according to laser diffraction and scanning electron micrograph. The highest ultraviolet light absorbance and anti-oxidant activities were obtained at 190oC treatment which were correlated to the highest phenolic group content. Application of the modified OLB at 3% w/w in a base cream formulation resulted in enhancement of the anti-UV activity to exceed SPF 50 with increasing anti-oxidant activity in the product. The work provides basis on modification of organosolv lignin for application as a potent functional additive in cosmeceutical products.